PENGARUH KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH DAN IKLIM ORGANISASI SEKOLAH TERHADAP DISIPLIN KERJA GURU DI SMKN 1 KOTA JAMBI - Putri Agustina; Mohamad Muspawi; Mulyadi Mulyadi (STKIP Pesisir Selatan, 2026)
This study aims to determine the effect of democratic principal leadership and school organizational climate on teacher work discipline at SMKN 1 Jambi City, both partially and simultaneously. This study employed a quantitative approach with an explanatory research design. The sample consisted of 61 teachers selected using probability sampling with a simple random sampling technique. Data were collected through questionnaires, observations, and documentation, then analyzed using descriptive statistics, prerequisite tests, multiple linear regression, t-tests, F-tests, and coefficient of determination tests using SPSS version 25. The results showed that democratic principal leadership had a positive and significant effect on teacher work discipline with a significance value of 0.050. School organizational climate also had a positive and significant effect on teacher work discipline with a significance value of 0.000. Simultaneously, both variables significantly affected teacher work discipline with an F value of 95.498 and an Adjusted R Square value of 0.759. The novelty of this study lies in examining the combined effect of democratic principal leadership and school organizational climate on teacher work discipline in the context of vocational high schools, which has received limited research attention, particularly at SMKN 1 Jambi City.